IMPROVEMENT OF NURANI SUPPORT SYSTEM IN NEW UZBEKISTAN - Fakhriddin Yormatov Joylovovich (Scholar Express Journal, 2022)
Uzbekistan, President, Advice of the elderly, Decree, Navruz, The olders, social protection, Single olders, Independence, labor honors, Memory and respect, Marriage, Kashkadarya, Namangan, Surkhandarya, The medicine, Trade Unions, kindness, Generosity, Grace
Keywords: measures; Surkhandarya; Advice; Navruz